The Puzzle of Militia Containment in Civil War. - Bolte, Brandon (International Studies Quarterly, 2021)
In most contemporary civil wars, governments collude with non-state militias as part of their counterinsurgent strategy. However, governments also restrict the capabilities of their militia allies despite the adverse consequences this may have on their overall counterinsurgent capabilities. Why do governments contain their militia allies while also fighting a rebellion? I argue that variation in militia containment during a civil war is the outcome of a bargaining process over future bargaining power between security or profit-seeking militias and states with time-inconsistent preferences. Strong states and states facing weak rebellions cannot credibly commit to not suppressing their militias, and militias with sufficient capabilities to act independently cannot credibly commit to not betraying the state. States with limited political reach and those facing strong rebellions, however, must retain militia support, which opens a "window of opportunity" for militias to augment their independent capabilities and future bargaining power. Using new data on pro-government militia containment and case illustrations of the Janjaweed in Sudan and Civil Defense Patrols in Guatemala, I find evidence consistent with these claims. Future work must continue to incorporate the agency of militias when studying armed politics, since these bargaining interactions constitute a fundamental yet undertheorized characteristic of war-torn states.